2011
DOI: 10.1029/2011ja016705
|View full text |Cite
|
Sign up to set email alerts
|

O+outflow channels around Venus controlled by directions of the interplanetary magnetic field: Observations of high energy O+ions around the terminator

Abstract: [1] Using the plasma and the magnetic field data measured by the ASPERA-4 (Analyzer of Space Plasma and Energetic Atoms) and the magnetometer (MAG) onboard Venus Express between June 2006 and December 2008, positions of high energy O + fluxes (>100 eV) near the Venus terminator are examined for two different interplanetary magnetic field (IMF) configurations: IMF nearly perpendicular to the Venus-Sun line (perpendicular IMF case) and IMF nearly parallel to it (parallel IMF case). In most of the perpendicular I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…A single interval of heavy ion flux was simultaneously seen with a plasmasheet crossing along orbits in the perpendicular cases, while multiple fluxes and plasmasheet crossings were observed in the parallel cases. Masunaga et al (2011) suggested that a stable, single plasmasheet along the interplanetary electric field direction is formed under the perpendicular IMF condition, while multiple, scattered plasmasheets appear to be formed for the parallel condition. The planetary ion acceleration mechanisms are therefore different even though the ion loss rate is about the same.…”
Section: Interaction Without the Solar Wind Convective Electric Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…A single interval of heavy ion flux was simultaneously seen with a plasmasheet crossing along orbits in the perpendicular cases, while multiple fluxes and plasmasheet crossings were observed in the parallel cases. Masunaga et al (2011) suggested that a stable, single plasmasheet along the interplanetary electric field direction is formed under the perpendicular IMF condition, while multiple, scattered plasmasheets appear to be formed for the parallel condition. The planetary ion acceleration mechanisms are therefore different even though the ion loss rate is about the same.…”
Section: Interaction Without the Solar Wind Convective Electric Fieldmentioning
confidence: 99%
“…Lundin (2011) used the orbit coordinate system (2006)(2007)(2008)(2009), and shifted the energy table to lower energies (to account for spacecraft potential) to derive an O + escape rate of 1.2 × 10 25 s −1 . For typical conditions, Masunaga et al (2011) derived a rate of (5.8 ± 2.9) × 10 24 s −1 for O + with energy > 100 eV. From photoelectron measurement on the field connected to the ionosphere, estimates the total ion outflow to be 2.2 × 10 23 s −1 .…”
Section: Impacts On the Atmospherementioning
confidence: 99%
“…This can explain why the majority of the observed flux ropes from this statistical analysis have similar widths and boundary normal directions to the ionospheric boundary wave. In addition, this scenario can also provide an explanation to the detection of atmospheric plasma outflows, which are observed mainly in the polar regions, for example, plasma clouds (Brace et al, ) and high‐energy O + fluxes (Masunaga et al, ). Both studies attributed their respective observations to the limitations of the PVO orbits and the upstream IMF orientations.…”
Section: Discussionmentioning
confidence: 98%
“…For example the heavy ion escape morphology at Venus is determined by the IMF direction (Fedorov et al, 2011;Nordstrom et al, 2013;Masunaga et al, 2011Masunaga et al, , 2013. On Mars solar wind precipitation seems to be a intermittent process, determined by the upstream conditions.…”
Section: Interplanetary Magnetic Field and Upstream Solar Wind Conditmentioning
confidence: 98%